Analisis Pengendalian Air Asam Tambang Menggunakan Kapur Tohor pada KPL AL-14 (Taman) Site Tambang Air Laya PT Bukit Asam TBK Tanjung Enim Sumatera Selatan - Supriyanto, Agus; Husni, Ahmad; Nursani, Rodiyah (PT. Publikasiku Academic Solution, 2025)
This study discusses the control of acid mine drainage (AMD) using quicklime (CaO) in the AL-14 (Taman) Sludge Settling Pond (KPL) at the Air Laya Mine site of PT Bukit Asam Tbk, Tanjung Enim, South Sumatra. Acid mine drainage is waste formed due to the oxidation of sulfide minerals, which can degrade water quality and damage the environment. This study aims to analyze the AMD control system, determine the ideal dosage of quicklime, calculate liming costs, and identify factors that influence daily lime requirements. The research method used is an experimental and observational approach, including laboratory tests using the jar test method and direct observations in the field during the period of April 28 to June 30, 2025. Tests were conducted on acid mine drainage samples with varying doses of quicklime (0–0.5 gr/L) to determine the optimum dose for increasing pH and reducing TSS. The test results showed that the ideal dose of quicklime to increase pH from 5.20 to the standard range (6–9) is between 0.1121–0.2812 gr/L, with an actual requirement of approximately 5 sacks/day. However, field usage reached an average of 10 sacks/day, causing cost overruns of up to Rp 381,600,000/month. The main factors influencing lime requirements are rainfall and runoff flow. This study provides recommendations for the implementation of an automatic monitoring system and blending system to improve the efficiency of AAT processing and reduce chemical waste.